Early indications of ANIT-induced cholestatic liver injury: Alteration of hepatocyte polarization and bile acid homeostasis. (December 2017) - Yang, Tingting; Mei, Huifang; Xu, Dengqiu; Zhou, Wang; Zhu, Xiaoyu; Sun, Lixin; Huang, Xin; Wang, Xue; Shu, Ting; Liu, Jia; Ding, Jiaxin; Hassan, H.M.; et al.
Abstract: Hepatocyte polarization is essential for biliary secretion, and loss of polarity causes bile secretory failure and hepatotoxicity. Here, we showed that alpha-naphthyl isothiocyanate (ANIT)-induced liver injury was accompanied by the dynamic interruption of bile acid homeostasis in rat plasma, liver and bile, which was characterized by the redistribution of bile acids in plasma and bile and a small range of fluctuations in the liver. Molecular mechanism studies indicated that these factors are dynamically mediated by the disruption of bile acid transporters and hepatic tight junctions. Dynamic changes in tight junction (TJ) permeability were observed by hepatobiliary barrier function assessment. Hepatocyte polarization was disrupted by ANIT before the development of cholestatic hepatotoxicity and alteration of bile acid metabolic profiles, which were assayed by high-performance liquid chromatography-tandem mass spectrometry, further verifying TJ deficiency. S1PR1 activation with SEW2871 reduced ANIT-induced liver injury by reducing the total serum bile acid concentration, liver functional enzyme activity and inflammation. Our data suggest that hepatocyte polarization plays an important role in maintaining bile acid homeostasis before the development of cholestatic hepatotoxicity and that TJs were more prominent in the early stage of cholestasis. S1PR1 may be a potential target for the prevention of drug-induced cholestatic liver injury. Highlights: Bile acid homeostasis was interrupted in the whole process of cholestasis induced by ANIT. Disruption of hepatocyte polarization occurred earlier than cholestatic hepatotoxicity in ANIT-induced rats. Hepatocyte tight junctions were more prominent at the early stage of cholestasis. SEW2871 alleviates ANIT-induced cholestasis in mice.